Comparative Analysis of Phishing Tools on Social Media Sites - Putu Candra Ariani; Kadek Sukma Jayanti; I Gede Bagastia Widi Atmaja; I Gusti Agung Ayu Ananda Dewi; Gede Arna Jude Saskara; I Made Edy Listartha (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
Social networks, often referred to as social media are a form of information technology development. Social networks are used by society in obtaining information, being a means of long-distance communication, as well as distributing information. However, behind the development of social media which has experienced significant developments, there are problems related to information security. Vulnerable to leakage of credential data and fraud becomes a negative impact due to the development of social media, one of the scams that often occurs on social media is phishing. Such scams are attempts to obtain, steal, or dig into someone's data through emails, text messages, and social media posts. A kun social media is targeted by perpetrators of phishing crimes because the account consists of sensitive data of social media users, one of the social media accounts that can be exposed the phishing attack is Facebook. Therefore, the problem studied in this study is how criminals use three different types of phishing tools to commit crimes. Social media users now understand how phishing works, where criminals use phishing tools to access social media accounts. The data obtained from this study is a comparison of the performance of phishing tools used in committing information crimes on the Facebook social media site, with the existence of these tools that are easy to use for phishing can be a supporting factor for perpetrators of phishing to user accounts freely.